2021
DOI: 10.2196/26443
|View full text |Cite
|
Sign up to set email alerts
|

mHealth App for Pressure Ulcer Wound Assessment in Patients With Spinal Cord Injury: Clinical Validation Study

Abstract: Background Clinical evaluation of a pressure ulcer is based on quantitative and qualitative evaluation. In clinical practice, acetate tracing is the standard technique used to measure wound surface area; however, it is difficult to use in daily practice (because of material availability, data storage issues, and time needed to calculate the surface area). Planimetry techniques developed with mobile health (mHealth) apps can be used to overcome these difficulties. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
(41 reference statements)
3
10
0
Order By: Relevance
“…For this reason, parameters have been developed which can be applied to wounds of different sizes to detect infection because infection is independent of wound size. In addition, there are already some suitable systems for documenting the geometric dimensions of the wound [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, since this information does not provide information about a possible infection, it is important to aim for an additional broadest possible infection detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, parameters have been developed which can be applied to wounds of different sizes to detect infection because infection is independent of wound size. In addition, there are already some suitable systems for documenting the geometric dimensions of the wound [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, since this information does not provide information about a possible infection, it is important to aim for an additional broadest possible infection detection.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the distance measurement of a depth camera, the limitation of the spacing in image detail between the visual and thermal images could be solved. By including a depth camera, the measurement of visual wound characteristics (e.g., wound size, shape) over time could also be possible [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The software foundation for this mobile system could be the algorithms proposed within this research as a proof of concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain applications have algorithms and clinical decision‐support tools to assist in determining the best treatment options, the type of wound products to use, the tracking of the wound healing progression and the next steps to take. These technologies for wound care have been developed and used for a number of years in Europe, the United States, Canada and the United Kingdom 21‐24 . Their use is also understood to be in the Australian context; however, we could not identify any literature reporting digital apps for an extensive range of wound types.…”
Section: Introductionmentioning
confidence: 98%
“…These technologies for wound care have been developed and used for a number of years in Europe, the United States, Canada and the United Kingdom. 21 , 22 , 23 , 24 Their use is also understood to be in the Australian context; however, we could not identify any literature reporting digital apps for an extensive range of wound types. Some studies have reported single wound types such as diabetic foot ulcers.…”
Section: Introductionmentioning
confidence: 99%